Clinical characteristics of children with omicron SARS-CoV-2 infection in Changchun, China from march to april 2022: A retrospective study - Li, Yan-chun; Ma, Zhen; Zhong, Hua-ying; You, Hai-long (Frontiers in Pediatrics, 2022)
Background: Recently, there was an outbreak in China of the Omicron (B.1.1.529) variant, the corresponding clinical characteristics of Chinese children with the Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection were then reviewed and summarized retrospectively. Methods: From March to April 2022, a total of 134 children infected with the Omicron variant were included in the study. Data such as sex, age, clinical symptoms, laboratory examinations, and imaging features were collected for further analyses. Results: Half of the children were male and the median age was 5.67 years. The most SARS-CoV-2 Omicron variant was identified in mild (122, 91%), and the most three frequent symptoms were as cough (108, 80.6%), fever (75, 56%), and sore throat (38, 28.4%). Among age groups, no significant difference was observed in the distribution of symptoms, and no statistical difference was found in different clinical types among sex or age groups. Laboratory examinations revealed that white blood cells, neutrophils, and hemoglobin decreased; and monocytes, C-reactive protein (CRP), and aspartate aminotransferase (AST) increased. Further analyses showed that neutrophils, hemoglobin, CRP, and AST exhibited significant differences among age groups. Radiological abnormalities were found in nine cases, with small patchy high-density shadows. Of the 76 cured cases discharged from the hospital, the median hospital stay was 13 days (mean, 12 days). Conclusions: In China, most children with Omicron SARS-CoV-2 infection have mild presentation. The findings of this study may help other districts improve the management of children with Omicron SARS-CoV-2 infection in China.